Work-Life-Balance and Digital Transformational Leadership Effects on Organizational Commitment Through Job Satisfaction for Hybrid Work Environment in Indonesia - Alessandro Alessandro; Ramadhania Ramadhania; Efa Irdhayanti; Ahmad Shalahuddin; Pramana Saputra (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This research were made to analyze and examine the effects of Work-Life-Balance and Digital Transformational Leadership on Organizational Commitment through the mediating roles of Job Satisfaction for hybrid work in Indonesia. This research were using survey research were used for data collecting, quantitative apprroach for analythic approch, and associative causal research for explanatory research. Population in this research consist of all every potential and real worker within in Indonesia, particulary who are working hybrid with the sample size for this research is 132 respondents. Non probability sampling were used in this research and purposive sampling were used with the following criteria of who aged above 17 years old, Indonesian citizen, work within Indonesia, and who have work in hybrid environment after pandemic at least 6 months. This research highlight the crutial role of hypotheses, which the result shows that Work-Life-Balance and Digital Transformational Leadership both have significant positive effects on and Organizational Commitment through Job Satisfaction among Indonesian hybrid employees, indicating that better balance and leadership enhance its commitment mainly through enhanced satisfaction. Whereas the Job Satisfaction mediates Digital Transformational Leadership stronger than Work-Life-Balance. Practically, employees ought to manage clear work-life boundaries, while the companies formalize the flexible hybrid policies. At last, it is recommended to include diverse samples and variables in hybrid work settings.